Expanding Dance Archives: Access, Legibility, and Archival Participation. (November 2020) - Laet, Timmy De
Abstract : The ample attention the archivisation of dance has received in recent years primarily focused on new archival formats that often rely on digital technologies or which relocate the archive into choreography and the dancing body. Even though these more experimental approaches are vital in broaching new avenues for dance archivisation, this article takes a step back by considering how existing archival structures can be expanded in order to increase both the accessibility and legibility of archive materials. Interweaving a personal account of doing archival research with a discussion of recent debates within both dance studies and archival science, the aim is to set up an interdisciplinary dialogue between two domains that have been operating in a remarkably isolated manner despite their mutual interests. Taking my cue from how the notion of 'participatory archives' is gaining prominence in archival practice and scholarship, I argue that enlarging the input of archival information may lead to a greater output with regard to both archival research and community outreach.